PENGEMBANGAN MODUL PEMBELAJARAN PEMECAHAN MASALAH DENGAN HEURISTIK REPRESENTASI GAMBAR UNTUK HASIL BELAJAR MATEMATIKA SISWA KELAS V SEKOLAH DASAR - Ronald Sahat Tua Simbolon; Mashudi Mashudi; Yulis Jamiah (Universitas Tanjungpura, 2021)
AbstractThe purpose of this research is to develop an instructional module of problem solving using pictorial representation heuristics for mathematics achievement of fifth grade students on the topic of fraction and proportion. The respondents were 39 fifth grade students from 2 classes of Tunas Bangsa Primary School, Kubu Raya Regency. The research method used the model of Borg and Gall. Data were collected by using questionnaires, validity sheets, survey and observation sheets by using Google Forms. The data gathered from questionaires and surveys were analyzed by counting the average of every aspect and then compared it to the suitable criteria and then were presented by using qualitative desciptive method. Pretest and post-test data were analyzed by using descriptive statistics by calculating the t-value for paired samples and the Cohen’s d effect size by using SPSS 22. The result was t= -11.602. It means that there is highly significant difference between instruction facilitated before the module was given and after it. The effect size obtained was 1.858 which means the instruction using the module has high power on improvement of learning outcome. In conclusion, this modul is qualified to be used.Keywords: Module, Heuristics, Problem Solving